The Influence of Profitability and Income Tax on Income Smoothing Rankings - Ratnaningrum Ratnaningrum (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2016)
Income smoothing is logical and rational action that managers attempt to reduce abnormal variation in earnings using special tools in accounting. The objective of this study is to investigate the influence of profitability and income tax on income smoothing rankings of the companies in basic industry and chemical sectors listed in Indonesia Stock Exchange. Statistical sample of the present study is formed from 45 companies in 2014. ROA is used as the proxy of profitability. In calculating the income smoothing, it is used Tucker-Zarowin (TZ) statistic for five year from the year 2010 to 2014 amounted to 225 firm-years observations. Income smoothing is measured by the negative correlation between the change in discretionary accruals and change in pre-discretionary income. The results from the hypotheses testing indicated that there is a negative and significant relationship between profitability and income smoothing. However, it is also found that there is no significant relationship between variables of income tax and income smoothing.